1995
DOI: 10.1042/bj3120135
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolarity stimulates prostaglandin synthesis and cyclooxygenase-2 expression in activated rat liver macrophages

Abstract: The effect of aniso-osmotic exposure on the level of inducible cyclooxygenase (Cox-2) and on prostanoid synthesis was studied in cultured rat liver macrophages (Kupffer cells). In lipopolysaccharide (LPS)- or phorbol 12-myristate 13-acetate-stimulated Kupffer cells, hyperosmotic (355 mosmol/l) exposure, due to addition of NaCl or impermeant sugars, markedly increased prostaglandin (PG) E2, D2 and thromboxane B2 synthesis in a time- and osmolarity-dependent manner. Increased prostanoid production was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 46 publications
1
47
0
1
Order By: Relevance
“…organs facing either extreme osmotic stresses or being encapsulated by rigid bone. However, recent studies have indicated that eicosanoid formation by LPS-stimulated rat liver macrophages (Kupffer cells) is critically dependent upon the ambient osmolarity and probably cell volume within a narrow range [2]. Thus, betaine availability and/or regulation of betaine transporter expression by osmolarity and other factors could be a potential site for the regulation of macrophages cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…organs facing either extreme osmotic stresses or being encapsulated by rigid bone. However, recent studies have indicated that eicosanoid formation by LPS-stimulated rat liver macrophages (Kupffer cells) is critically dependent upon the ambient osmolarity and probably cell volume within a narrow range [2]. Thus, betaine availability and/or regulation of betaine transporter expression by osmolarity and other factors could be a potential site for the regulation of macrophages cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation with endotoxin they produce a variety of cytokines, lipid mediators and radicals. In rat liver macrophages, lipopolysaccharide (LPS)-induced prostaglandin E and thromboxane B formation and cyclooxygenase-2-expression is stimulated about 7-fold when ambient osmolarity increases from 300 to 350 mosmol/1 [2]. This sensitive and potent osmoregulation of prostanoid synthesis suggests that cell volume homeostasis may be a critical factor for macrophage function.…”
Section: Introductionmentioning
confidence: 99%
“…Rat Kupffer cells were prepared by collagenase-pronase perfusion and separated by a single Nycodenz gradient and centrifugal elution as described previously [3,16]. Cells were cultured in RPMI 1640 medium supplemented with 10% heat-inactivated fetal calf serum (FCS) for 48 h. The experiments were performed during the following 24 h using Krebs-Henseleit hydrogen carbonate buffer (pH 7.4) containing 10 mmol/l glucose.…”
Section: Isolation and Culture Of Kupffer Cellsmentioning
confidence: 99%
“…Recent studies have indicated that endotoxin enhances the expression of inducible cyclooxygenase-2 (Cox-2) [2][3][4][5][6], which results in the increased formation of prostanoids by Kupffer cells and other macrophages [3,[7][8][9]. Interestingly, lipopolysaccharide (LPS)-induced prostaglandin E2, D2 and thromboxane B2 formation and Cox-2 expression are stimulated up to 10-fold when ambient osmolarity increases from 300 to 350 mosmol/1 [3]. This remarkably sensitive and potent osmoregulation suggested that cell volume homeostasis is critical for Kupffer cell function.…”
Section: Introductionmentioning
confidence: 99%
“…This involves not only the regulation of osmoregulatory genes, such as the expression of aldose reductase [2] or speci¢c sodium-coupled transporters for myo-inositol [3,4], betaine [4,5] and taurine [4,6], but also the expression of genes encoding proteins that are not linked to osmoregulation. Examples of the latter are the rapid increases in mRNA levels for L-actin [7], inducible nitric oxide synthetase [8], cyclooxygenase-2 [9], c-jun [10] and phosphoenolpyruvate carboxykinase [11].…”
Section: Introductionmentioning
confidence: 99%